Insights into the Relationship Between Products and Services Coming from Biology. (4th September 2013) - Allen, Timothy F.; Shaw, Duncan; Allen, Peter C.; Spohrerin, James; Ing, David; Wilby, Jennifer
<x xml:space="preserve">Abstract</x> This paper examines the relationship between product manufacturing and service production using the lenses of concepts from biology and ecology. Social science tends to contrast rather than compare. Biological science compares across levels rather than establishing contrasts. Biological systems are tangible but complex, anchors that ground biology as it explores multilevel structures using multiple logical types. This tendency towards unity over division is offered as a complement to social scientific divisiveness in the services literature. Discourses of relative scale and level can help descriptions of the product–service relationship, which otherwise holds the discourse to a low levels of analysis about local logical types. We use examples of human ecological occupancy of landscapes, cleaner fish services, roots serviced by rhizospheres, origins of photosynthesis, dust mites and the misnomer of 'ecosystem services' to develop the conceptualisation of products and services. We conceptualize products and services as unified in being opposite sides of the same coin that flips with a shift in the level of analysis. Copyright © 2013 John Wiley & Sons, Ltd.